THE RELATIONSHIP BETWEEN VITAMIN D INTAKE AND PLASMA C-REACTIVE PROTEIN LEVELS AND APPENDICULAR SKELETAL MUSCLE INDEX IN ADULTS WITH OBESITY - Issabella Nisrina Pratiwi; Ninik Mudjihartini; Wahyu Ika Wardhani (SOSIOEDUKASI, 2026)
Obesity is commonly associated with chronic low-grade inflammation and alterations in skeletal muscle mass, increasing the risk of sarcopenic obesity. Vitamin D deficiency and elevated C-reactive protein (CRP) levels are frequently observed in individuals with obesity and may contribute to impaired muscle metabolism. This study aimed to examine the relationship between vitamin D intake, plasma C-reactive protein (CRP) levels, and the Appendicular Skeletal Muscle Index (ASMI) among obese adults at Universitas Indonesia Hospital (RSUI). An analytical cross-sectional design was employed involving 70 obese adults aged 18–59 years. Vitamin D intake was assessed using a semi-quantitative food frequency questionnaire, plasma CRP levels were measured using enzyme-linked immunosorbent assay (ELISA), and ASMI was determined using bioelectrical impedance analysis. Data were analyzed using univariate, bivariate, and multivariate statistical methods. The results showed that most participants had inadequate vitamin D intake and elevated plasma CRP levels, indicating the presence of systemic inflammation. No significant association was found between vitamin D intake and CRP levels or between vitamin D intake and ASMI. However, plasma CRP levels demonstrated a weak but statistically significant association with ASMI. These findings suggest that inflammation plays a more prominent role than vitamin D intake in influencing skeletal muscle mass among obese adults, highlighting the multifactorial nature of sarcopenic obesity.